The impact of UiTM Raub campus upon local economy : A study on students’ expenditure / Noor Amira Syawani Abd Rahman...[et. al.] - Abd Rahman, Noor Amira Syawani; Ridzuan, Mohd Rozaimy; Kong, Lai Kuan; Ju, Soon Yew (Universiti Teknologi MARA Cawangan Pahang, 2019)
UiTM Raub Campus started operating since 29 November 2015. This newly open Pahang branch campus can accommodate around 3000 students. Looking at the huge number of students, this study aims to examine the impact of UiTM Raub Campus students’ expenditure toward the local economy. Through a questionnaire survey, a total of 240 responses were collected in May, 2018. The results showed that the expenses incurred by the students have contributed positively to local economy.